The Amish secret wish - Hilton, Laura V., 1963- (Hilton, Laura V., 1963- Hidden Springs novel., 2021)
"Waitress Hallie Brunstetter has a secret: she writes a popular column for her Amish paper under the pen name GHB. When Hallie receives a letter from a reader asking to become her pen pal, she reluctantly agrees. She can't help but be drawn to the compassionate stranger, never expecting him to show up in Hidden Springs looking for GHB . . . or for him to be quite so handsome in real life. But after losing her beau in a tragic accident, Hallie won't risk her heart or her secrets again"--Provided by publisher.